Inhibition of Aminotransferases by Aminoethoxyvinylglycine Triggers a Nitrogen Limitation Condition and Deregulation of Histidine Homeostasis That Impact Root and Shoot Development and Nitrate Uptake - Le Deunff, Erwan; Beauclair, Patrick; Deleu, Carole; Lecourt, Julien (Frontiers in Plant Science, 2019)
BBackground and Aims: Although AVG (aminoethoxyvinylglycine) is intensely used to decipher signalling in ethylene/indol-3-acetic acid (IAA) interactions on root morphogenesis, AVG is not a specific inhibitor of aminocyclopropane-1-carboxylate synthase (ACS) and tryptophan aminotransferase (TAA) and tryptophan aminotransferase related (TAR) activities since it is able to inhibit several aminotransferases involved in N metabolism. Indeed, 1 mM glutamate (Glu) supply to the roots in plants treated with 10 μM AVG partially restores the root growth. Here, we highlight the changes induced by AVG and AVG + Glu treatments on the N metabolism impairment and root morphogenetic program. Methods: Root nitrate uptake induced by AVG and AVG + Glu treatments were measured by a differential labelling with 15NO3- and 15Nglutamate. In parallel a profiling of amino acids (AA) was performed to decipher the impairment of AA metabolism. Key Results: 10 μM AVG treatment increases K15NO3 uptake during root growth inhibition whereas 10 μM AVG + 1 mM 15Nglutamate treatment inhibits K15NO3 uptake and increases 15Nglutamate uptake during partial root growth restoration. This is explained by a nitrogen (N) limitation condition induced by AVG treatment and a N excess condition induced by AVG + Glu treatment. AA levels were mainly impaired by AVG treatment in roots, where levels of Ser, Thr, α-Ala, β-Ala, Val, Asn and His were significantly increased. His was the only amino acid for which no restoration was observed in roots and shoots after glutamate treatment suggesting important control of His homeostasis on aminotransferase network. Results were discussed in light of recent findings on the interconnection between His homeostasis and the general amino acid control system (GAAC) in eukaryotes. Conclusions: These results demonstrate that AVG concentration above 5 M is a powerful pharmacological tool for unravelling the involvement of GAAC system or new N sensory system in morphological and metabolic changes of the roots in leguminous and non-leguminous plants.